Pengaruh Digital Influencer dan Intensitas Event Terhadap Tingkat Pengetahuan Khalayak di Instagram - Debhora Krisna Cinditya P (CoverAge: Journal of Strategic Communication, 2020)
The rise of the use of social media Instagram triggers a microcelebrity phenomenon that makes Instagram social media an advertising space. Djarum 76 sees a new opportunity in carrying out promotional activities through Instagram to raise the potential of Djarum 76 target villages spread in Central Java and DIY in the 2019 period. This study aims to determine whether there is an influence between digital influencers on social media Instagram and intensity Festival Heppiii 76 roadshow event to the level of public knowledge about the potential of Djarum 76 fostered villages in Central Java Region 2019 period. This study uses theories of uses and gratifications, digital influencer concepts, events, level of knowledge, integrated marketing communication, sales promotion, and personal sales. This research uses an explanatory quantitative approach with a positivistic paradigm. The results showed the effect of digital influencer activity on the level of knowledge of 0.218. The influence of the intensity of the event off air on the level of knowledge of 0.34. Simultaneous test results show the F value of significance of 0,000, which means that together with the digital influencer activity variable and the intensity of off air events affect the level of public knowledge about the potential of the Djarum 76 Guided Village in Central Java in the 2019 period.